Conservation Genomics of Wild Red Sage (Salvia miltiorrhiza) and Its Endangered Relatives in China: Population Structure and Interspecific Relationships Revealed From 2b-RAD Data - Zhou, Xuan; Zhang, Zhi-Cheng; Huang, Yan-Bo; Xiao, Han-Wen; Wu, Jun-Jie; Qi, Zhe-Chen; Wei, Yu-Kun (Frontiers in Genetics, 2021)
Red sage (Salvia miltiorrhiza) is a widely used medicinal plant for treatment of cardiovascular and cerebrovascular diseases. Because of excessive excavation by huge market demand and habitat loss by human activities, the wild population resources of S. miltiorrhiza have reduced drastically in recent years. Meanwhile, population condition of two closely related species S. bowleyana and S. paramiltiorrhiza were in a trend of decreasing due to their potential replacement of S. miltiorrhiza. Particularly, S. paramiltiorrhiza was threatened and endemic to a small region in eastern China. However, to date there has been no conservation genetic research reported for wild S. miltiorrhiza population and its endangered relatives. Assess the wild germplasm diversity for S. miltiorrhiza and its related species would provide fundamental genetic background for cultivation and molecular breeding of this medicinally important species. In the present study, we investigated the genetic diversity, population structure, and intra/inter-specific differentiation of S. miltiorrhiza and above two relatives using 2b-RAD genome-wide genotyping method. By investigating 81 individuals of S. miltiorrhiza, 55 individuals of S. bowleyana and 15 individuals of S. paramiltiorrhiza from 23 locations in China, we obtained 23,928 SNPs in total. A comparatively high genetic diversity was observed in S. miltiorrhiza (π = 0.0788, He = 0.0783 ± 0.0007). The observed and expected heterozygosity in populations of these three species ranged from 0.0297 to 0.1481 and 0.0251 to 0.831, respectively. Two major lineage groups were detected in the examined S. miltiorrhiza populations. The results indicated that Dabie Mountain as a genetic diversity center of S. miltiorrhiza and possible complex inter-specific genetic exchange/hybridization occurred between S. miltiorrhiza and the two relatives. We suggest that strategic conservation and germplasm preservation should be considered not only for wild populations of S. miltiorrhiza, but also for its related S. bowleyana and S. paramiltiorrhiza.